2019
DOI: 10.1177/0091647119837016
|View full text |Cite|
|
Sign up to set email alerts
|

Cultural Humility with Religious and Spiritually Diverse Women of Color Clients: A Psychometric Analysis

Abstract: Cultural humility, as part of a therapist’s multicultural orientation, can help facilitate a strong working alliance with clients across diverse cultural backgrounds. Given that little research has attended to how the intersections of race/ethnicity, gender, and religion/spirituality (R/S) influence counseling dyads, we tested the factor structure and provided evidence for the reliability and construct validity of the Cultural Humility Scale (CHS) with a sample of R/S diverse women of color ( N = 288). To our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 86 publications
3
7
0
Order By: Relevance
“…We found that specific multicultural training had a positive relationship with CH; thus, CITs who completed more multicultural courses possessed higher CH. This finding aligns with literature that argues that multicultural training can help clinicians shift from cultural competence to CH (DeBlaere et al., 2019). This finding also implies that in addition to being a disposition, CH can be fostered by multicultural training.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that specific multicultural training had a positive relationship with CH; thus, CITs who completed more multicultural courses possessed higher CH. This finding aligns with literature that argues that multicultural training can help clinicians shift from cultural competence to CH (DeBlaere et al., 2019). This finding also implies that in addition to being a disposition, CH can be fostered by multicultural training.…”
Section: Discussionsupporting
confidence: 91%
“…However, the relationship between multicultural counseling competence and CH remains unclear. In a recent study, client's perception of therapists’ CH was positively associated with perception of multicultural counseling competence (DeBlaere et al., 2019). Still, some have suggested an inverse relationship between multicultural counseling competence and CH (Hook et al., 2017; Mosher et al., 2017).…”
Section: Cultural Humility and Multicultural Trainingmentioning
confidence: 98%
“…All of the other studies found to use the Cultural Humility Scale examined internal consistency and reported estimates for the full scale and subscales ranging from .83 to .94. Evidence of convergent validity was also shown in studies that reported significant correlations between the Cultural Humility Scale and both the Cross-Cultural Counseling Inventory-Revised (CCCI-R; DeBlaere et al, 2019;Hook et al, 2016) and the Counselor Rating Form-Short (Hook et al, 2016).…”
Section: Cultural Humility Scalementioning
confidence: 71%
“…Subsequent studies have continued to use the 12-item Cultural Humility Scale and have also found good psychometric properties. Franco and McElroy-Heltzel (2019) and DeBlaere et al (2019) conducted confirmatory factor analyses with samples of different racial/ethnic identities and validated the original internal structure of the scale. All of the other studies found to use the Cultural Humility Scale examined internal consistency and reported estimates for the full scale and subscales ranging from .83 to .94.…”
Section: Cultural Humility Scalementioning
confidence: 99%
“…In counseling treasures in Asia, a cultural approach has entered and is an essential part of efforts to increase the effectiveness of counseling services. Research in Asia shows the trend of counseling developments toward using spiritual and religious values (DeBlaere et al, 2019; Pandya, 2018) and using a transformative approach in developing effective and efficient counseling services (Kravia & Pagliano, 2016). As a continent inhabited by most of the Muslim population, researchers in Asia have also transformed in developing counseling services for Muslims by incorporating Islamic values as a reference in applying counseling techniques (Cook-Masaud & Wiggins, 2011; Hamidi et al, 2010; Isgandarova, 2012).…”
Section: Resultsmentioning
confidence: 99%